Additional to “Rubiaceae of Thailand. A pictorial guide to indigenous and cultivated genera” - Puff, Christian; Chayamarit, Kongkanda (Thai Forest Bulletin (Botany), 2014)
Descriptions, notes and colour plates of four monotypic (monospecific) genera (Clarkella Hook. f., Gardeniopsis Miq., Hyptianthera Wight & Arn. and Morindopsis Hook. f.) are presented which had not been included in “Rubiaceae of Thailand. A pictorial guide to indigenous and cultivated genera” (Puff et al., 2005). Morindopsis laotica is reduced to a synonym of M. capillaris.